Crosstalk between Brassinosteroid and Redox Signaling Contributes to the Activation of CBF Expression during Cold Responses in Tomato - Pingping Fang; Yu Wang; Mengqi Wang; Feng Wang; Cheng Chi; Yanhong Zhou; Jie Zhou; Kai Shi; Xiaojian Xia; Christine Helen Foyer; Jingquan Yu (MDPI AG, 2021)
Brassinosteroids (BRs) play a critical role in plant responses to stress. However, the interplay of BRs and reactive oxygen species signaling in cold stress responses remains unclear. Here, we demonstrate that a partial loss of function in the BR biosynthesis gene DWARF resulted in lower whilst overexpression of DWARF led to increased levels of C-REPEAT BINDING FACTOR (CBF) transcripts. Exposure to cold stress increased BR synthesis and led to an accumulation of brassinazole-resistant 1 (BZR1), a central component of BR signaling. Mutation of BZR1 compromised the cold- and BR-dependent increases in CBFs and RESPIRATORY BURST OXIDASE HOMOLOG 1(RBOH1) transcripts, as well as preventing hydrogen peroxide (H2O2) accumulation in the apoplast. Cold- and BR-induced BZR1 bound to the promoters of CBF1, CBF3 and RBOH1 and promoted their expression. Significantly, suppression of RBOH1 expression compromised cold- and BR-induced accumulation of BZR1 and related increases in CBF transcripts. Moreover, RBOH1-dependent H2O2 production regulated BZR1 accumulation and the levels of CBF transcripts by influencing glutathione homeostasis. Taken together, these results demonstrate that crosstalk between BZR1 and reactive oxygen species mediates cold- and BR-activated CBF expression, leading to cold tolerance in tomato (Solanum lycopersicum).